Nolen-Hoeksema's abnormal psychology - Jennings, Heather; Jennings, Heather (New York: McGraw Hill, 2024)
"Abnormal Psychology connects proven scholarship with student performance. Through an integrated, person-alized learning program, the eighth edition gives students the insight they need to study smarter and improve performance. McGraw-Hill Education Connect® is a digital assignment and assessment platform that strengthens the link between faculty, students, and course work. Connect for Abnormal Psychology includes assignable and as-sessable videos, quizzes, exercises, and interactivities, all associated with learning objectives for Abnormal Psychology, Eighth Edition"--
Includes bibliographical references and index.
Keywords: Psychology, Pathological -- Textbooks; Mental illness -- Textbooks